The survival guide for kids with LD* : *learning differences - Fisher, Gary L.; Cummings, Rhoda Woods (Minneapolis, MN : Free Spirit Pub., 2002)
Discusses how children with'learning differences' can get along better in school, set goals, and plan for the future
Includes bibliographical references (p. 84-94) and index
Keywords: Learning disabled children -- Education -- United States -- Handbooks, manuals, etc. -- Juvenile literature; Learning disabilities -- United States -- Handbooks, manuals, etc. -- Juvenile literature; Learning disabilities